2019
DOI: 10.1111/jphs.12331
|View full text |Cite
|
Sign up to set email alerts
|

Parental self‐medication of antibiotics for children in Jordan

Abstract: Objectives This study aims to describe the prevalence and predictors for parental antibiotics self‐medication of their children and to characterize their knowledge, practice and attitude within this area. Methods This is a cross‐sectional study which targeted parents of children between the ages of 1–12 years. Parents were asked to fill out an online validated questionnaire that aimed to assess their knowledge, practice and attitude to self‐medication of children with antibiotics. Key findings In this study, 3… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
21
0
6

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(28 citation statements)
references
References 29 publications
1
21
0
6
Order By: Relevance
“…The results from this current study are in line with our 2006 results, 13 as patients continue to self‐medicate with antibiotics for self‐reported viral infection (ie, influenza and the common cold) and believing that it could irradiate such infections. Similar antibiotics self‐medication practices were also reported in several studies 9,27,35 . Interestingly, this study reported a significant increase in patients accessibility to pharmacies as a source of antibiotic supply compared with results from 2006 13 …”
Section: Discussionsupporting
confidence: 84%
“…The results from this current study are in line with our 2006 results, 13 as patients continue to self‐medicate with antibiotics for self‐reported viral infection (ie, influenza and the common cold) and believing that it could irradiate such infections. Similar antibiotics self‐medication practices were also reported in several studies 9,27,35 . Interestingly, this study reported a significant increase in patients accessibility to pharmacies as a source of antibiotic supply compared with results from 2006 13 …”
Section: Discussionsupporting
confidence: 84%
“…However, it was only 4.0% in urban U.S., 12.1% in suburban U.S. [ 53 ], and 22.7% in the Greece [ 23 ]. As for other Asian countries, it was 43.9%, 39.2% and 29.8% in Saudi Arabia [ 54 ], Jordan [ 55 ] and Vietnam [ 56 ], respectively. It’s worth noting that nationality was associated with the practices of PSMA in this study, showing that Chinese parents were more likely to self-medicate with antibiotics for children than Occidental parents, the same as the above findings conducted in separate countries [ 18 , 20 , 23 , 48 , 52 , 53 ].…”
Section: Discussionmentioning
confidence: 98%
“…2 For example, the use of non-prescribed antibiotics for the treatment of viral infection (ie, influenza and common colds) is not an appropriate indication. [3][4][5] Antibiotics consumed inappropriately by the people not only result in wastage of resources but also carry potential lifethreatening severe adverse effects and the emergence of bacteria with extensive drug resistance; 6,7 the reason behind this practice is the easy availability of antibiotics. Several studies reported that people from low and middleincome countries (LMICs) buy antibiotics easily without a proper prescription, and this is the most critical driver of antimicrobial overuse.…”
Section: Introductionmentioning
confidence: 99%